2005
DOI: 10.1634/stemcells.2004-0123
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Mesenchymal Stem Cells Can Express Insulin and Key Transcription Factors of the Endocrine Pancreas Developmental Pathway upon Genetic and/or Microenvironmental Manipulation In Vitro

Abstract: Multipotential stem cells can be selected from the bone marrow by plastic adhesion, expanded, and cultured. They are able to differentiate not only into multiple cell types, including cartilage, bone, adipose and fibrous tissues, and myelosupportive stroma, but also into mesodermal (endothelium), neuroectodermal, or endodermal (hepatocytes) lineages. Our goal was to characterize the multipotential capacities of human mesenchymal stem cells (hMSCs) and to evaluate their ability to differentiate into insulin-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
163
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(171 citation statements)
references
References 65 publications
3
163
1
4
Order By: Relevance
“…other important pancreas transcription factors, and the consequent production of insulin in agreement with Moriscot's conclusions about MSCs [36]. We observed that the morphology of BTC-MSCs changed from spindle-like to flat epithelial-like cells.…”
supporting
confidence: 91%
“…other important pancreas transcription factors, and the consequent production of insulin in agreement with Moriscot's conclusions about MSCs [36]. We observed that the morphology of BTC-MSCs changed from spindle-like to flat epithelial-like cells.…”
supporting
confidence: 91%
“…Fibroblast-like cells emerging from pancreatic islets have been shown to be able to differentiate into insulin-expressing cells. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] To evaluate the ability of hPIDM cells to differentiate into a pancreatic endocrine phenotype, cells were cultured for 21 days in a medium for endocrine differentiation. Under these conditions, cells formed clusters that remained adherent to culture plates for the first week, but afterward detached acquiring an isletlike morphology (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…15 However, controversial data on the ability of mesenchymal stem cells to differentiate into insulin-producing cells both in vitro and in vivo have been reported. [19][20][21][22][23] Major interest has been recently raised by the evidence that insulinproducing cells can be obtained following the in vitro expansion of an intermediate mesenchymal proliferating cell population apparently derived from a reversible epithelialmesenchymal transition of pancreatic b-cells. 24, 25 Similar results have been obtained from the exocrine compartment of human pancreas.…”
mentioning
confidence: 99%
“…In ex vivo regeneration therapy, the patients' own bone marrow stem cells are transiently removed and differentiated into b-cells in vitro (Lechner & Habener 2003, Moriscot et al 2005 whereas in vivo regeneration therapy uses the patients' own cells to regenerate impaired tissues (Zulewski et al 2001, Gao et al 2003. In vivo regeneration therapy is more cost-effective, has fewer side effects, and is more ethically and clinically acceptable; therefore, it may offer the greatest potential therapeutic value to diabetic patients, if effective protocols could be developed.…”
Section: Introductionmentioning
confidence: 99%